(untitled) (Research, Society and Development, 2022)
The progress test provides the students the capacity to know their evolution following the teaching-learning progress, identifying their problems. It is believed that adherence to this test will depend on how the student understands its benefits in the learning. The aim of this study was to evaluate students’ knowledge about the progress test and to evaluate the association between adherence and performance in progress test with sociodemographic and academic factors. The methodology was a cross-sectional study, by applying a structural questionnaire, evaluating the variables of students’ socio-demographic, academic factors and assessing the students’ knowledge about the test, through a questionnaire in Likert model. The study population consisted of students of four health courses of Faculdade Pernambucana de Saúde. Adherence to progress test was 84,9%, being higher among medical students. Variable “working beside studying” was associated with lower adherence to the test. Students agreed with most of the benefits statements relating to progress tests. Good adherence was identified to progress test, being higher among medical students and those who did not have a job. Therefore, students showed a positive view of the test, identifying its benefits. The variable “working beside studying” was associated with lower adherence to the test.